Supplementing the Forest Health National Aerial Survey Program with Remote Sensing during the COVID-19 Pandemic: Lessons Learned from a Collaborative Approach. Issue 2 (3rd November 2021) - Hanavan, Ryan P; Kamoske, Aaron G; Schaaf, Abigail N; Eager, Tom; Fisk, Haans; Ellenwood, Jim; Warren, Kayanna; Asaro, Christopher; Vanderbilt, Brian; Hutten, Karen; Leatherman, Lila; Finco, Mark; et al.
Abstract: The COVID-19 pandemic has created unprecedented challenges in the way the USDA Forest Service conducts business. Standard data collection methods were immediately challenged due to travel restrictions and due to uncertainty regarding when it would be safe to return to a "business as usual" approach. These challenges were met with an inspiring collaboration between forest health specialists directly involved in the annual Aerial Detection Survey (ADS) program and remote sensing specialists from the Forest Service and academia. This group worked together to generate informative training materials, new workflows, and weekly help sessions to directly address problems that arose during this capacity building exercise. Small ad hoc teams were created to identify regionally specific program resources to enhance remote sensing utilization while supplementing information gaps where aerial detection surveys were either limited or not possible. The lessons learned from this challenge provide an opportunity to continue the exploration of combining ADS, remote sensing, and field data to deliver comprehensive information for managing the nation's forests, while applying what is working and learning and growing from both successes and limitations.